Siglec-15 Is an Immune Suppressor and Potential Target for Immunotherapy in the Pre-Metastatic Lymph Node of Colorectal Cancer - Du, Hang; Tang, Jingling; Li, Xiaoyun; Wang, Xinjun; Wu, Liyun; Zhang, Ruyi; Hu, Pingsheng; Yang, Yuan (Frontiers in Cell and Developmental Biology, 2021)
Lymph node metastasis indicates a poor prognosis in colorectal cancer. To better understand the underlying mechanisms of lymph node metastasis, we analyzed transcriptome characteristics of the pre-metastastic lymph node, a putative microenvironment favorable for the seeding and proliferation of cancer cells. Thus, we tried to compare and elucidate the transcriptional and immune characteristics of sentinel lymph nodes (SN) with matched non-sentinel lymph nodes (NSN) in colorectal cancer patients. In this study, a total of 38 pairs of SN and NSN were collected, in which 26 pairs of non-metastastic lymph nodes were subjected to RNA-seq and bioinformatics analysis for the gene expression profiles. There were 16 differentially expressed genes between SN and NSN being identified, including 9 up-regulated and 7 down-regulated genes in SN. Gene Ontology (GO) classification analysis revealed that the differentially expressed genes were mainly involved in leukocyte differentiation, chemokine secretion, and immune system regulation. In the meantime, gene set enrichment analysis (GSEA) showed that immune-related signaling pathways, such as TGF-β signaling and TNF-α/NF-κB signaling, were enriched in NSN, while cell proliferation related signaling pathways were enriched in SN, including MYC signaling and G2M checkpoint signaling. We further identified SIGLEC15 as a top up-regulated gene in SN. However, RNAscope assay showed that SIGLEC15 was not largely co-expressed with M2 macrophage marker CD163. We then selected 8 pairs of lymph nodes for further cytological studies. Flow cytometry analysis revealed that Siglec-15 was expressed on all myeloid cell subsets. The relative expression of SEGLEC15 (SN/NSN) was correlated with the microsatellite instability (MSI) status in colorectal cancer patients. Further studies found that siRNA-mediated silencing of SLGLEC15 can enhance the anti-tumor function of T cells, as indicated by cytokine release analysis. In conclusion, we here presented a first report on the gene expression profiling of the pre-metastastic lymph node in colorectal cancer. The findings in this study suggest that SIGLEC15 plays an important role in SN immunosuppression. SEGLEC15 silencing could be a therapeutic strategy for restoring T cell function in tumor sentinel lymph nodes.